Advances in Clinical Phonetics. - Ball, Martin J. (Martin John) (Studies in speech pathology and clinical linguistics ;, 1996)
Advances in Clinical Phonetics focuses on important developments in phonetic description. Recent years have seen increasing developments in phonetic description, in both instrumental and impressionistic approaches. Not restricted to the phonetics of normal speech, clinical phoneticians and speech scientists working with disordered speech, have been at the forefront of recent work. Some instrumental developments (such as electropalatography), and some transcription developments (such as extIPA symbols), have been spearheaded by clinical phoneticians. The present collection describes and explore.